Hubungan Metode Mengajar Dosen, Keterampilan Belajar, Sarana Belajar dan Lingkungan Belajar dengan Prestasi Belajar Mahasiswa - H.M. Farid Nasution (Universitas Negeri Malang, 2016)
This study was aimed at finding out the relationships between teaching methods, learning skills, learning facilities, learning environment, and students' achievement. A stratified proportional random sample consisted of 329 drawn from 1180 students of IAIN Sumatera Utara, Medan. Data were collected using a questionnaire and then analyzed statistically by correlation and regression techniques. The result revealed that there was a significant correlation between those variables